Inclusión financiera en Perú: desarrollo bajo una perspectiva multidimensional - Zamalloa Llerena, Juan Carlos (2017)
This research aims to contribute and deepen the understanding of the explanatory and influential factors on the financial inclusion of the individuals in Peru. Hence the investigation considerate this as a multidimensional phenomenon composed of access and usage of financial services, trust of individuals and the regulation of financial services. In this perspective the study analyzes the relationship between financial inclusion and its dimensions with socioeconomic and geographic variables, thus it contemplate a review of the most relevant literature, the situation of access and use of financial services in Peru, the main regulations and the constraints that the financial markets are facing. The results show that education is an explanatory variable only when is evaluated with the aggregated financial inclusion variable but not so with the components, and wealth and access to public services are determinants of financial inclusion at every level. Additionally, the outcomes suggest that financial regulation generates unequal financial development. Keywords: Financial Inclusion, Peru, Financial Markets, Financial System, Financial Development